A mathematical model of a nuclear reactor with delay depending on the power of the reactor - Bučys, Kostas; Grigolienė, Rasa; Janutėnienė, Jolanta; Švitra, Donatas (Lietuvos matematikos rinkinys, 2002)
There is analysed the problem of the stability of the reactor using a nonlinear mathematical model. By the method of D-decomposition there is done linear analysis and obtained a region of asymptotic stability D0 and the region D2 in which there appear a stable periodical solution. The nonlinear analysis of the model was done with the help of the theory of bifurcations. There is received an approximate periodical solution of one frequency of the model and determined the `degree of harmonicity’’ of the solution.